Development of an E-Module Assisted by Augmented Reality on Digestive System Material to Improve Elementary Students' Critical Thinking Skills - Adinda Zulfa Kamila; Aldina Eka Andriani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Digital teaching materials, such as e-modules in basic science that utilise technology, have not yet been implemented in learning, resulting in 56% of students having low critical thinking skills. This study aims to describe the development design and to test the feasibility and effectiveness of an Augmented Reality-assisted e-module to improve the critical thinking skills of V-grade students at SDN Pendrikan Lor 03, Semarang City. This type of research is Research & Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 25 V-grade students. The data collection technique used non-test methods (observation, interviews, questionnaires, and documentation) and test methods (pretest and posttest). The data analysis technique used normality tests, homogeneity tests, t-tests, and N-Gain tests. The feasibility of the e-module assisted by Augmented Reality is proven by the assessment of the material expert validator of 91% and the media expert validator of 95% in the very feasible category, supported by the results of the teacher response questionnaire analysis of 92.5% and the student response questionnaire of 90.3% in the very feasible category. The effectiveness of the e-module assisted by Augmented Reality is evidenced by an increase in pretest and posttest scores of 20.26, supported by a t-test result of 0.000, and an N-Gain score of 0.5314, which falls within the medium range. The research on the e-module assisted by Augmented Reality for the digestive system material was successfully developed, is very feasible, and is effective in improving the critical thinking skills of V-grade students at SDN Pendrikan Lor 03, Semarang City.